2001
DOI: 10.1159/000054687
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biological Activity of Gonadotropin-Releasing Hormone Isoforms Isolated from Rat and Hamster Brains

Abstract: Rat and hamster brain tissues were used to investigate the possible existence of a follicle stimulating hormone (FSH)-releasing factor with similar characteristics to the lamprey gonadotropin-releasing hormone III (lGnRH-III) form proposed in previous reports. The present studies involved isolation and purification of the molecule by high-performance liquid chromatography (HPLC), identification by radioimmunoassay, sequence analysis by automated Edman degradation, mass spectrometry and examination of biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
3
18
1
1
Order By: Relevance
“…Moreover, when rat pituitary cells were perfused with doses (10 -7 to 10 -5 M) of lGnRH-III, gonadotropin secretion was increased without any indication of a selective secretion of FSH (Kovacs et al, 2002). These data is in agreement with in vitro results obtained from rat hemipituitaries incubated with doses (10 -9 to 10 -7 M) of lGnRH-III (Montaner et al, 2001). The contradictory results obtained by different laboratories, may be explained by experimental condition, the influence of the presence or absence of steroid in the in vivo models, and data interpretation (Kovacs et al, 2002).…”
Section: Lamprey Gnrh-iiisupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, when rat pituitary cells were perfused with doses (10 -7 to 10 -5 M) of lGnRH-III, gonadotropin secretion was increased without any indication of a selective secretion of FSH (Kovacs et al, 2002). These data is in agreement with in vitro results obtained from rat hemipituitaries incubated with doses (10 -9 to 10 -7 M) of lGnRH-III (Montaner et al, 2001). The contradictory results obtained by different laboratories, may be explained by experimental condition, the influence of the presence or absence of steroid in the in vivo models, and data interpretation (Kovacs et al, 2002).…”
Section: Lamprey Gnrh-iiisupporting
confidence: 90%
“…However, lGnRH-III was not d e t e c t e d i n r a t s a n d o t h e r r o d e n t s b y r e v e r s e -p h a s e -H P L C f o l l o w e d b y R I A , o r b y performing two successive HPLC steps to prevent the coelution of GnRH peptides (Gautron et al, 2005;Montaner et al, 1999;Montaner et al, 2001). When rats were infused (i.v.)…”
Section: Lamprey Gnrh-iiimentioning
confidence: 99%
“…Yu et al (2000) reported selective FSH-releasing activity in fractions of gel-purified hypothalamic extracts that could be neutralized by antisera against lGnRH and proposed that the putative FSH-RH fractions were lGnRH-III or a closely related peptide. However, Montaner et al (2001) were unable to detect selective FSHreleasing activity in rat and hamster hypothalamic extracts purified by HPLC. At least two other reports have failed to demonstrate selective FSH release by lGnRH-III in rat pituitary cells (Lovas et al 1998, Montaner et al 2001.…”
Section: Discussionmentioning
confidence: 88%
“…Although not isolated in mammals to date, an alternative form of GnRH, lamprey GnRH-III (lGnRH-III) (Sower et al 1993), has been reported to selectively stimulate the release of FSH in rodents (Yu et al 1997) and in cattle during the luteal phase of the estrous cycle (Dees et al 2001). However, several other studies, both in vitro (Yu et al 1997, Lovas et al 1998, Montaner et al 2001, Kovacs et al 2002 and in vivo (Kovacs et al 2002), have questioned the ability of lGnRH-III to selectively release FSH in rodents. Clearly, the existence of a distinct mammalian FSH-RH could have far-reaching implications in both medicine and agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on mid-luteal intact cows [15] and barrows [16] reported that l-GnRH-III only stimulates the release of LH and does not affect FSH. Still other studies indicated that treatment with 1-GnRH-III did not cause any increase in the levels of either FSH or LH in rodent brain tissues [17] or in gilts [1], but stimulated the secretion of both gonadotropins in rat pituitary cells [18] and ovariectomized cows [15]. To date, no studies have been conducted to explore the influence of l-GnRH-III on the secretion of the different reproductive hormones in gilts and sows at the same time.…”
Section: Introductionmentioning
confidence: 99%